Cancer immunotherapy with check point inhibitor can cause autoimmune adverse events due to loss of Treg homeostasis. (August 2020) - Kumar, Prabhakaran; Saini, Shikha; Prabhakar, Bellur S.
Abstract: Regulatory T-cells (Tregs) can facilitate immune evasion by tumor cells by dampening anti-tumor immunity. Reduced Teff/Treg ratio and enhanced Treg functional activity have been observed in patients suffering from different types of cancers, and attenuated Treg numbers/functions can serve as prognostic indicators. Normally, Tregs play an essential role in the maintenance of immune tolerance and prevention of autoimmunity. The most common immune checkpoint blockers (ICB) targeting co-inhibitory receptors such as anti-CTLA4 (ipilimumab and tremelimumab) and anti-PD1 (pembrolizumab and nivolumab)/anti-PD-L1 (atezolizumab) have achieved unprecedented success in cancer treatment by facilitating an effective anti-tumor immune response, at least in part, by blocking Treg mediated immunosuppression. While ICBs have shown remarkable success in cancer immunotherapy, immune-related adverse events (IRAEs) arising from ICB have forced consideration of ways to maintain immune homeostasis post ICB treatment. Preclinical models of IRAEs have shown a negative correlation between Treg numbers and IRAEs. Therefore, understanding the "ying-yang" role of Tregs in the regulation of autoimmunity and anti-tumor immunity is critical to provoking an effective anti-tumor response while maintaining immune homeostasis. Studies aimed at developing effective approaches to minimize IRAEs without compromising anti-tumor immunity are underway. Herein, we discuss 1) the critical role of key co-inhibitory receptors on Treg homeostasis and tumor tolerance; 2) how co-receptor blockade by cancer immunotherapy can lead to autoimmune adverse events; and 3) recently emerging management strategies to minimize autoimmune adverse events arising from ICB.